Strikingly low prevalence of pituitary incidentalomas in a teaching hospital in Uruguay - Pineyro, Maria M.; Sosa, Natalia; Rivero, Florencia; Tripodi, Diego; Negrotto, Matias; Lima, Ramiro (Frontiers in Endocrinology, 2023)
Pituitary incidentalomas are an occurrence documented in 10.6% of post-mortem examinations, 4-20% of computed tomography (CT) scans, and 10-38% of magnetic resonance imaging (MRI) cases, primarily consisting of microincidentalomas (<1cm in size). However, the prevalence of pituitary incidentalomas in Uruguay remains unexplored. This study aimed to ascertain the prevalence of pituitary incidentalomas at our Hospital. Methods: In this investigation, we retrospectively identified patients who underwent brain CT and MRI at our hospital over a one-year span due to conditions other than suspected or known pituitary disorders. The time frame covered was from January 1 to December 31, 2017. Our analysis encompassed all scans, and we conducted interviews with patients discovered to have pituitary incidentalomas. Furthermore, we conducted biochemical assessments in accordance with clinical and imaging traits.Results: During the study period,, a total of 3894 patients underwent imaging procedures. Of these, 1146 patients underwent MRI scans, and 2748 underwent CT scans. The mean age was 53.1 ± 19 years, with a relatively even distribution between genders (50.6% women). The majority of imaging requisitions originated from the emergency department (43%), followed by outpatient clinics (29%), and inpatient wards (28%). Common reasons for imaging requests included trauma (20.4%), headaches (11.3%), and stroke (10.9%). Among these cases, two pituitary incidentalomas were detected, resulting in a prevalence of 5 cases per 10,000 individuals annually (0.051%). Both of these cases were initially identified through CT scans, with subsequent MRI scans performed for further assessment. The final diagnoses were a vascular aneurysm and a sellar meningioma, with the latter This is a provisional file, not the final typeset article patient also exhibiting secondary hypothyroidism. Notably, no instances of pituitary adenomas were encountered.Conclusions: The prevalence of pituitary incidentalomas within our hospital was notably low. Further research is necessary to more comprehensively investigate the occurrence of pituitary incidentalomas in our country.